Implementation of Singing Method in Improving Learning Outcomes of Names of Angels Material at Guppi Al Jihad Balangbuki Elementary School - Jannah, Zahratul; Yusnita (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of the singing method in improving student learning outcomes on the material of the names of angels at MI Guppi Al Jihad Balangbuki. The singing method is applied as a fun, interactive, and creative learning strategy so that students can more easily understand and remember the material. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and learning outcome tests. The subjects of the study were students of MI Guppi Al Jihad who were studying the material on the names of angels and their duties. The results of the study showed that the singing method was able to increase students' motivation and active participation in the learning process. In addition, students found it easier to memorize the names of angels and their duties compared to conventional methods. This increase can be seen from the evaluation results which showed that most students experienced an increase in understanding after the application of the singing method. Thus, the singing method can be used as an effective alternative learning method, especially in Islamic Religious Education subjects at the elementary school level. It is hoped that this study can be a reference for teachers in creating more interesting and meaningful learning for students. The results of the study showed that the singing method had a positive impact on improving students' understanding of the material on the names of angels, increasing students' memory and making it easier to memorize the names of angels. The support provided by the teacher, such as guiding questions, helps students build a better understanding of the material. In addition, students are more active in the learning process and are able to recognize the names of angels correctly. The application of the singing method can facilitate understanding of concepts and develop students' social and emotional skills